Influence of type of mesh fixation in endoscopic totally extraperitoneal hernia repair (TEP) on long-term quality of life - Horisberger, Karoline; Jung, M. K.; Zingg, U.; Schöb, Othmar (World journal of surgery, 2013)
Laparoscopic total extraperitoneal mesh repair (TEP) of inguinal hernia has become well accepted with low recurrence and high patient satisfaction rates. However, inguinal pain has also been reported. Source of this pain has been suggested to be the fixation method, especially the use of tacks. Introduction of fibrin glue and absorbable tacks were suggested to lower chronic pain and inguinal discomfort rates. This study analyses the different methods of fixation.